Unilateral Maximal Isometric Hex Bar Pull Test: Within-Session Reliability and Lower Body Force Production in Male and Female Freeski Athletes - McPhail, Jonathan; Gonçalves, Basílio A. M.; Spörri, Jörg; Linnamo, Vesa (Frontiers in Sports and Active Living, 2021)
The aim of the study was to (1) assess the within-session reliability of a unilateral isometric hex bar pull (UIHBP) maximal voluntary contraction (MVC) test and, (2) determine unilateral isometric absolute peak force (PFabs) and relative peak force (PF) values in freeski athletes. Twenty-one male and eight female academy to national team freeskiers performed the novel UIHBP MVC task on a force plate and PFabs and relative PF were assessed (1000 Hz). Within-session measures of PFabs offered high reliability on left and right limbs for males (ICC = 0.91–0.94, CV = 2.6–2.2%) and females (ICC = 0.94–0.94, CV = 1.4–1.6%), while relative PF measures showed good to high reliability in both left and right limbs for males (ICC = 0.8–0.84, CV = 2.6–2.2%) and females (ICC = 0.92–0.90, CV = 1.4–1.7%). We observed significantly lower PFabs (p < 0.001) and relative PF (p < 0.001) in females compared to males. No statistical difference was found between left and right limbs in males and females in PFabs (p = 0.98) and relative PF measures (p = 0.93). The UIHBP MVC test appears to be a reliable method for assessing PFabs and relative PF in male and female freeski athletes.